2021
DOI: 10.7554/elife.67267
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 facilitates extinction of conditioned fear

Abstract: Insulin-like growth factor-1 (IGF-1) plays a key role in synaptic plasticity, spatial learning and anxiety-like behavioral processes. While IGF-1 regulates neuronal firing and synaptic transmission in many areas of the central nervous system, its signaling and consequences on excitability, synaptic plasticity, and animal behavior dependent on the prefrontal cortex remain unexplored. Here, we show that IGF-1 induces a long-lasting depression of the medium and slow post-spike afterhyperpolarization (mAHP and sAH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…shown that fear conditioning decreases excitability, whereas extinction training enhances excitability and decreases medium-and slow AHP (Santini et al, 2008;Maglio et al, 2021). At the IC, chronic ethanol consumption has shown to decrease excitability and to increase AHP (Luo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…shown that fear conditioning decreases excitability, whereas extinction training enhances excitability and decreases medium-and slow AHP (Santini et al, 2008;Maglio et al, 2021). At the IC, chronic ethanol consumption has shown to decrease excitability and to increase AHP (Luo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, the current study demonstrated that intra-mPFC IGF-1 infusion produces antidepressant-like effects in the LPS-induced depression model mice via mTORC1 activation. Furthermore, IGF-1 increases cell surface GluA1 protein levels in the mPFC [ 15 ], and exogenous IGF-1 has also been reported to increase excitability and potentiate synaptic transmission in mPFC layer V pyramidal neurons [ 15 , 46 ]. Additionally, the frontoparietal cortex of IGF-1 null mice have reduced dendritic spine density in layers II/III and V pyramidal neurons [ 47 ], while IGF-1 treatment rescued decreased PSD-95 protein levels and dendritic spine density in the somatosensory cortex of a mouse model of cyclin-dependent kinase-like 5 deficiency disorder [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 is a polypeptide hormone mainly produced in the hepatocytes and exerts its effect through high-affinity binding to the IGF-1R, located on the cell surface of target tissues [5]. IGF-1 affects a wide variety of biological activities such as somatic cell development, cell differentiation, cortical neuronal activity, regulation of brain development, and is involved, directly and indirectly, in longevity [6][7][8][9][10][11]. Interestingly, IGF-1 has a very potent physiological effect in vivo; however, its effects in vitro are relatively weak unless other hormones or growth factors are present [5].…”
Section: Introductionmentioning
confidence: 99%